Amiodarone Use Is Associated With Increased Risk of Stroke in Patients With Nonvalvular Atrial Fibrillation. Issue 19 (May 2015) - Chen, Wei-Chun; Chen, Wei-Cheng; Chen, Chih-Yu; Wu, Biing-Ru; Cheng, Wen-Chien; Lin, Kuo-Hung; Hsia, Te-Chun; Chen, Wei; Chen, Chia-Hung; Muo, Chih-Hsin; Liao, Wei-Chih; Li, Chia-Hsiang; et al.
<x xml:space="preserve">Abstract</x> Abstract Atrial fibrillation (AF), the most common sustained arrhythmia requiring treatment worldwide, is one of the major causes of ischemic stroke. Although amiodarone is commonly used for rhythm control in AF, its relationship with stroke has rarely been addressed. We evaluated 16, 091 patients who were diagnosed with AF (Classification of Diseases, 9th Revision, Clinical Modification [ICD-9-CM] 427.31 and 427.32) between 1998 and 2011; the date of AF diagnosis was set as the index date. Patients with a history of stroke (ICD-9-CM 430–438) who received amiodarone before the index date or during the following 30 days, or who experienced stroke within 30 days of receiving amiodarone were excluded. Finally, 7548 patients with AF were included in this study and divided into 2 groups according to whether they received amiodarone (Anatomical Therapeutic Chemical code C01BD01) during the study period. The risk of ischemic stroke in AF patients receiving amiodarone was 1.81-fold (95% confidence interval [CI] 1.52–2.16), 1.79-fold (95% CI 1.50–2.14), and 1.78-fold (95% CI 1.49–2.13) higher than in those who did not receive amiodarone, according to crude, Model 1, and Model 2 Cox proportional hazard regression models, respectively. In a demographically stratified analysis, the risk of ischemic stroke was significantly higher in patients aged <65 years, with no comorbidities, who were also taking digoxin or had a low CHA2DS2VASc score. Amiodarone treatment is associated with an increased risk of stroke in patients with AF, especially in those who have an initial low risk of stroke. Antiplatelet drugs and warfarin could reduce the stroke risk in AF patients receiving amiodarone. However, as the combination of digoxin and amiodarone increases the risk of stroke in these patients, the combination of these 2 drugs should be avoided.